2017
DOI: 10.3892/or.2017.5988
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy induction enhances tetrandrine-induced apoptosis via the AMPK/mTOR pathway in human bladder cancer cells

Abstract: Tetrandrine, a bisbenzylisoquinoline alkaloid isolated from the roots of Stephania tetrandra is a traditional Chinese medicine and exerts anticancer capacity in various types of cancers. Previous studies have shown that tetrandrine induces apoptosis in bladder cancer cells via activation of the caspase cascade. However, the underlying mechanism has not yet been reported. Autophagy is a cellular process involved in the degradation of broken proteins and aging organelles to maintain homeostasis. Recent studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…The induction of apoptosis by tetrandrine has been performed in many types of cancer cells, including pancreatic cancer cells, [ 95 ] leukaemia cells [ 101 ] and non‐small‐cell lung cancer (NSCLC) cells. [ 102 ] An apoptosis mediated by tetrandrine occurs mainly through the regulation of the following signalling pathways: (1) the AMPK/mTOR [ 60 ] ; (2) the PI3K/AKT [ 81 ] ; (3) the YAP [ 82 ] ; (4) the PI3K/AKT/mTOR [ 69 ] ; (5) the MAPKs [ 55 ] ; (6) the Wnt/β‐catenin [ 83 ] ; (7) the Wnt/cadherin [ 65 ] ; (8) the ERK/MAP kinase and ERK [ 84 ] ; (9) the PARP [ 41 ] ; (10) the caspases/beclin I/LC3‐I/II [ 61 ] ; (11) the caspase cascade and mitochondrial [ 59 ] ; (12) the death receptor pathway [ 64 ] , and any more.…”
Section: The Anticancer Activity Of Tetrandrinementioning
confidence: 99%
See 2 more Smart Citations
“…The induction of apoptosis by tetrandrine has been performed in many types of cancer cells, including pancreatic cancer cells, [ 95 ] leukaemia cells [ 101 ] and non‐small‐cell lung cancer (NSCLC) cells. [ 102 ] An apoptosis mediated by tetrandrine occurs mainly through the regulation of the following signalling pathways: (1) the AMPK/mTOR [ 60 ] ; (2) the PI3K/AKT [ 81 ] ; (3) the YAP [ 82 ] ; (4) the PI3K/AKT/mTOR [ 69 ] ; (5) the MAPKs [ 55 ] ; (6) the Wnt/β‐catenin [ 83 ] ; (7) the Wnt/cadherin [ 65 ] ; (8) the ERK/MAP kinase and ERK [ 84 ] ; (9) the PARP [ 41 ] ; (10) the caspases/beclin I/LC3‐I/II [ 61 ] ; (11) the caspase cascade and mitochondrial [ 59 ] ; (12) the death receptor pathway [ 64 ] , and any more.…”
Section: The Anticancer Activity Of Tetrandrinementioning
confidence: 99%
“…Autophagy, a ‘self‐eating’ phenomenon, is a cellular process involved in the degradation of damaged proteins and aging organelles to maintain homeostasis [ 60 ] and is associated with cell death. [ 129 ] Research shows that tetrandrine induces autophagy in human bladder cancer T24 and 5637 cell lines by increasing the expression of LC3‐II, up‐regulating the protein levels of AMPK and ACC, and down‐regulating mTOR‐related proteins in a time‐ and concentration‐dependent manner via the regulation of the AMPK/mTOR signalling pathways.…”
Section: The Anticancer Activity Of Tetrandrinementioning
confidence: 99%
See 1 more Smart Citation
“…This process is stimulated by various stimuli, including nutrients [ 71 , 72 ]. In fact, in bladder cancer cells, autophagy plays an important role in pathological processes and signaling pathways via external stimuli, including natural products [ 73 , 74 ]. With regard to the relationship between autophagy and GTPs, an in vitro study showed that the latter inhibited epirubicin-induced autophagy [ 75 ].…”
Section: Bladder Cancer and Green Teamentioning
confidence: 99%
“…Surprisingly, H89/tetrandrine-induced cell death could not be completely reversed by the apoptosis inhibitor z-VAD-fmk, which implies that apoptosis was not the only contributor. Autophagy is involved in type-II programmed cell death, particularly in apoptosis-deficient cells, and may be exploited to suppress tumor growth [ 47 , 48 ]. Our results showed that H89/tetrandrine-induced cell death was moderately diminished by the autophagy inhibitor, which demonstrates the contribution of autophagy to cell death in response to treatment.…”
Section: Discussionmentioning
confidence: 99%